NETWORK PHARMACOLOGY AND MOLECULAR DOCKING-BASED EXPLORATION OF RUBIACEOUS PLANTS FOR BREAST CANCER: PHYTOCHEMICALS, PRECLINICAL STUDIES, AND REGULATORY PERSPECTIVES - OMKAR TIPUGADE; JYOTIRAM A SAWALE; NAMDEO JADHAV (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Cancer remains a global health challenge due to the limitations of conventional therapies, including drug toxicity and resistance. This study aims to explore the anticancer potential of Rubiaceous plant species by investigating their bioactive phytochemicals, molecular targets, and pharmacological pathways, with a particular focus on breast cancer. Materials and Methods: A network pharmacology approach was employed to identify therapeutic compounds and their molecular targets. Disease-related targets were sourced from GeneCards and the Therapeutic Target Database (TTD). Cytoscape and STRING were used to construct interaction networks. Gene Ontology (GO) and KEGG pathway enrichment analyses were performed to elucidate biological functions and pathways. Molecular docking studies were conducted to assess the binding affinities of key phytoconstituents. Results: A total of 1,435 biological processes and 173 pathways were associated with breast cancer. Molecular docking revealed Quercetin as the most potent compound with a binding affinity of -34.92 kcal/mol. Other compounds such as Acacetin, Resveratrol, and Apigenin exhibited lower, but significant, binding affinities. Rubiaceous plants, including Alibertia myrciifolia, Anthocephalus cadamba, and Camptotheca acuminata, were identified to contain flavonoids, alkaloids, and anthraquinones with demonstrated anticancer effects, including apoptosis induction and DNA damage. Conclusion: Rubiaceous plants exhibit promising anticancer potential through multi-target mechanisms. Regulatory oversight is crucial to ensure the safety and efficacy of these herbal therapies. Further research is warranted to isolate active compounds, understand their molecular mechanisms, and validate their clinical relevance for integration into modern oncology.